Fiqh Versi Alam Melayu: Satu Analisis Sejarah - Abdul Rahim, Rahimin Affandi; Kahal, Siti Maimunah; Yusof @ Salleh, Muhammad Yusri (Jurnal Fiqh, 2016)
This study discusses how Islam became the most important episode in the history of the Malay World. The arrival of Islam that had modified the world view of Arab communities in the Arab World brought about the same changes to the Malay World. The Islamisation process resulted in knowledge development which produced paradigms vialable for Malay society. The basic traditions formulated by Islamic theologians in the 16th-18th centuries has become the core foundation for the Islamic Malay World until today. This is a theory from Middle East fiqh that has been changed to suit the culture and identities of the Malay World and as the guidance of life for the Malay community. The various Malay World fiqh sources have made it to become unique and very special and this study pays particular reference to the Malay World Fiqh. Thus, this version of Fiqh is analyzed based on the history of the Malay World with its abundant Islamic knowledge that emerged from the process of Islamisation. The analysis shows that Islamisation has produced a Malay World version of fiqh as an important channel in the creation of knowledge and characteristics of the community and has contributed to the rapid development of Islam.